2020
DOI: 10.3390/nano10091812
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Commercial Metal Oxide Nanomaterials: Crystalline Phase, Particle Size and Specific Surface Area

Abstract: Physical chemical characterization of nanomaterials is critical to assessing quality control during production, evaluating the impact of material properties on human health and the environment, and developing regulatory frameworks for their use. We have investigated a set of 29 nanomaterials from four metal oxide families (aluminum, copper, titanium and zinc) with a focus on the measurands that are important for the basic characterization of dry nanomaterials and the determination of the dose metrics for nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…This may be because nanoparticles are composed of one or more crystallites. The crystallite size is assumed to be the size of a coherently diffracting domain, and it is not necessarily the same as the particle size because of which particle size calculated using TEM micrographs is always higher than the crystallite size estimated using XRD data . Moreover, multiple nanocrsytallites determined by XRD spectra overlap to form a particle estimated by TEM images which explains higher values of particle sizes as compared to crystallite size …”
Section: Results and Discussionmentioning
confidence: 99%
“…This may be because nanoparticles are composed of one or more crystallites. The crystallite size is assumed to be the size of a coherently diffracting domain, and it is not necessarily the same as the particle size because of which particle size calculated using TEM micrographs is always higher than the crystallite size estimated using XRD data . Moreover, multiple nanocrsytallites determined by XRD spectra overlap to form a particle estimated by TEM images which explains higher values of particle sizes as compared to crystallite size …”
Section: Results and Discussionmentioning
confidence: 99%
“…In most cases (Ni-03–Ni-08), the mean equivalent diameter was close to the nominal value provided by the manufacturer, but it was considerably lower for two samples (Ni-01, Ni-02), Figure S4 . A previous study of four families of other commercial metal oxide nanoparticles has also demonstrated that a significant number of samples have primary particle sizes that differ substantially from those reported by the manufacturer [ 26 ]. Note that the particle size distributions as assessed by the standard deviation are quite broad for most samples.…”
Section: Data and Resultsmentioning
confidence: 99%
“…Doping IONPs with another metal ion could inhibit their phase transition and retain their amorphous nature, hence maintaining the increased surface area [9][10][11]. Another common challenge with using IONPs is their tendency to aggregate, which decreases their specific surface area [12]. This means that the application of nanoparticle adsorbents in fixed-bed columns or at an industrial scale is limited.…”
Section: Introductionmentioning
confidence: 99%